Daridra Perspektif Susastra Hindu - I Putu Agus Aryatnaya Giri; Kadek Dwi Sentana Putra; Kadek Agus Yoga Dwipranata; I Ketut Wiratmaja (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Poverty in general often reveals a negative side that haunts life, especially the life of someone who is not culturally educated to think revolutionary, especially related to a better life welfare. From the perspective of Hindu religious literature, of course poverty is very interesting to review, especially in breaking through the cultural paradigm of thinking that wallows in